Digital Marketing Strategy, Muslim Consumer Loyalty and Managerial Decisions on Company Profitability at Batik Jlantir - Maulana Rosyid Zidan; Aditya Dwi Prasetyo; Ade Gunawan; Hendri Hermawan Adinugraha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The company considers many factors and decides digital marketing strategies and non-digital marketing strategies to achieve maximum profit. In addition, the company maintains a good relationship with its environment and offers a good service to its customers. The manager's role also determines the company and its short-term or long-term profit goals. Therefore, this study aims to examine Batik Jlantir's digital marketing strategy, Muslim customer loyalty, and management decisions that affect the company's profitability. This research method uses a quantitative approach to various causal relationships. The population of this research is all stakeholders of Batik Jlantir company and the research sample is 96 people. This study shows that there is a positive and significant relationship between Batik Jlantir's digital marketing strategy, Muslim customer loyalty, and management decisions on company productivity. The study shows the implications for the stakeholders of Batik Jlantir to adopt appropriate policies to maintain good customer service, improve digital marketing and achieve company profitability. Keywords: Profitability, Digital Marketing, Batik Jlantir